Stability and the competition-dispersal trade-off as drivers of speciation and biodiversity gradients - Pellissier, Loïc (Frontiers in Ecology and Evolution, 2015)
The geography of speciation is one of the most contentious topics at the frontier between ecology and evolution. Here, building on previous hypotheses, I propose that ecological constraints on species co-existence mediate the likelihood of speciation, via a trade-off between competitive and dispersal abilities. Habitat stability, as found in the tropics, selects for the evolution of stronger competitive abilities. Since resource investment in competitive and dispersal abilities should trade off, high competition in stable habitats reduces species dispersal ability, decreasing effective population sizes. In smaller local populations, higher fixation rates of molecular substitutions increases the likelihood of speciation. Higher species diversity triggers more speciation by further increasing the spatial structuring of populations and decreasing effective population sizes. Higher resource specialization also trades-off with dispersal ability and could account for speciation at higher trophic levels. Biotic interactions would therefore promote parapatric speciation and generate spatial patterns in diversity such as the latitudinal diversity gradient. I discuss the main evidence for this mechanism and emphasize the need for studies coupling ecology and speciation theory within landscapes.